Cultivating a Landscape of Peace Iroquois-European Encounters in Seventeenth-Century America - Dennis, Matthew (Cornell University Press, 2018)
This book examines the peculiar new worlds of the Five Nations of the Iroquois, the Dutch, and the French, who shared cultural frontiers in seventeenth-century America. Viewing early America from the different perspectives of the diverse peoples who coexisted uneasily during the colonial encounter between Europeans and Indians, he explains a long-standing paradox: the apparent belligerence of the Five Nations, a people who saw themselves as promoters of universal peace.In a radically new interpretation of the Iroquois, Dennis argues that the Five Nations sought to incorporate their new European neighbors as kinspeople into their Longhouse, the physical symbolic embodiment of Iroquois domesticity and peace. He offers a close, original reading of the fundamental political myth of the Five Nations, the Deganawidah Epic, and situates it historically and ideologically in Iroquois life. Detailing the particular nature of Iroquois peace, he describes the Five Nations' diligent efforts to establish peace on their own terms and the frustrations and hostilities that stemmed from the fundamental contrast between Iroquois and European goals, expectations, and perceptions of human relationships